Hedge and Alder-Based Agroforestry Systems: Potential Interventions to Carbon Sequestration and Better Crop Productivity in Indian Sub-Himalayas - Parmar, Brajendra; Vishwakarma, Anand; Padbhushan, Rajeev; Kumar, Amarendra; Kumar, Rajkishore; Kumari, Ragini; Kumar Yadav, Brahmdeo; Giri, S. P.; Kaviraj, Megha; Kumar, Upendra (Frontiers in Environmental Science, 2022)
Agroforestry systems (AFSs) have potential to combat climate change and to ensure food security. AFSs can sequester carbon and amend the organic matter, thereby enhancing the crop productivity. Carbon sequestration depends on the type of AFSs, climate, cropping pattern, and management practices. The aim of this study was to evaluate different AFSs for their potential to sequester carbon and impact on soil organic matter (SOM) in the eastern sub-Himalayas, India. Hedge-, alder-, and guava-based AFSs were established along with control (without any tree), and the maize–mustard–potato cropping pattern was followed in each AFS. Soil samples were collected after the fifth crop cycle and further analyzed. The results showed that crop productivity was significantly higher in all the AFSs than control. On average, soil organic carbon (SOC) was found to be significantly higher by 62 and 64% in hedge-based AFSs as compared to guava-based AFSs and control, respectively, and at par with alder-based AFSs. Particulate organic carbon (POC) was higher in all the three AFSs than in the control. For microbial biomass carbon (MBC) and microbial biomass nitrogen (MBN) contents, the trend of AFSs was expressed as alder-based AFS > hedge-based AFS > guava-based AFS > control. Hedge- and alder-based AFSs had higher SOC stocks than guava-based AFSs and control. Carbon dioxide equivalent (CO2 eq.) emissions were greater in control than hedge-based AFSs (35.2 Mg ha−1), followed by alder-based AFSs (28.6 Mg ha−1), and the lowest was observed in guava-based AFSs. On an average, hedge species accumulated more nitrogen (N), phosphorus (P), and potassium (K), which were 60, 12, and 28 kg ha−1 yr−1, respectively. This conclusively proved that AFSs were significantly affecting SOM pools and crop productivity and had a significant role in carbon retention in the soil. Overall, hedge- and alder-based AFSs retained higher soil carbon, and hence, hedge- and alder-based AFSs may be promoted to achieve climate-smart agriculture practices in the acid soils of the Indian sub-Himalayan region.